Analysis of Student Learning Outcomes Using Team Game Tournament (TGT) Type Cooperative Learning in Elementary Schools - Nisa, Silvia Khoerun; Mulyati, Riska Nurutami; Kawali, Nur Baida; Alur, Hayati (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
This research aims to analyze the effectiveness of the Teams Games Tournament (TGT) learning model on student mathematics learning outcomes. The research method used is literature study, by collecting and analyzing various relevant academic sources, including journals, articles and research reports. Literature analysis shows that the application of the TGT model consistently has a positive impact on students' mathematics learning outcomes at various levels of education. The TGT model increases learning motivation, student engagement, and understanding of mathematical concepts. The study also found that TGT helps develop social and cooperative skills among students. The results of this literature review indicate that the TGT model is an effective learning strategy and can be recommended for use by educators in an effort to improve student mathematics learning outcomes. Researchers suggest that implementing the TGT model can be an effective alternative learning strategy for improving mathematics learning outcomes in elementary schools. Further research is recommended to explore the application of this model to other subjects and different levels of education.